Resource Utilization of Rare-Earth-Rich Biomass and Ammonia Nitrogen Effluent from Mining - Weiye Li; Zhiqiang Chen; Zhibiao Chen; Liujun Feng; Cailing Yu (Land)
The post-treatment of heavy metal-enriched plants in mining areas and the purification of ammonia and nitrogen pollution in water bodies are significant for the ecological environment of ionic rare earth mining areas. Herein, we focused on the biochar production potential of Dicranopteris pedata, characterizing biochar prepared by an oxidative modification process and an iron modification process. We conducted adsorption experiments to comparatively investigate the adsorption performance of biochar on NH4+ and studied the fertilizer application and migration toxicity of the adsorbed biochar for rare earth elements (REEs). Results indicated that ~332.09 g of biochar could be produced per unit area of D. pedata under 100% clipping conditions. The Brunauer–Emmett–Teller (BET) specific surface area of oxidized biochar (H2O2BC) increased, and the pore size of iron-modified biochar increased. The adsorption behavior of biochar toward NH4+ was well represented by the pseudo-second-order and Langmuir models. H2O2BC demonstrated the strongest adsorption of NH4+ with maximum theoretical equilibrium adsorption of 43.40 mg·g−1, 37.14% higher than that of pristine biochar. The adsorption process of NH4+ on biochar is influenced by various physicochemical mechanisms, including pore absorption, electrostatic attraction, and functional group complexation. Furthermore, the metal ions in the biochar did not precipitate during the reaction process. The adsorbed NH4+ biochar promoted the growth of honey pomelo without risking REE pollution to the environment. Therefore, it can be applied as a nitrogen-carrying rare earth fertilizer in low rare earth areas. This study provides a theoretical basis and technical support for the phytoremediation post-treatment of rare earth mining areas and the improvement of ammonia nitrogen wastewater management pathways in mining areas.